Medical laboratory accreditation in a resource-limited district health centre laboratory, Addis Ababa, Ethiopia - Daniel M. Desalegn; Boja D. Taddese; Nebiyou Yemanebrhane; Mulye S. Getahun; Kumera T. Kitila; Tariku T. Dinku; Kassahun D. Asferie; Elizabeth A. Wolde; Gemechis B. Tura; Tilahun B. Mersha; Alemayhu W. Rorissa; Daniel D. Wondimagegnehu; et al. (African Journal of Laboratory Medicine, 2019)
Background: Improving the quality of medical laboratory services is a high priority in many countries. However, quality management systems for laboratories in resource-limited settings are often inadequate.